Effect of a Baduanjin intervention on the risk of falls in the elderly individuals with mild cognitive impairment: a study protocol for a randomized controlled trial - Ziyi Wu; Yuxing Kuang; Yiwen Wan; Jiao Shi; Shuqian Li; Rui Xia; Mingyue Wan; Shangjie Chen (BMC, 2023)
Abstract Background Falls are a global public problem and may be an important cause of death in older adults. However, older adults with mild cognitive impairment(MCI) are more likely to fall and suffer more damage than older adults with normal cognitive function, which shows the importance of preventing falls. More and more evidence shows that Baduanjin can improve the balance function of the elderly and reduce the risk of falls in the elderly with MCI, but the mechanism is still unclear. The main purpose of this study is to verify the intervention effect of Baduanjin training on the risk of falls in elderly people with MCI and to elucidate the underlying mechanism of Baduanjin training in reducing the risk of falls in MCI patients. Methods In this prospective study, outcome assessor-blind, three-arm randomized controlled trial, a total of 72 eligible participants will be randomly allocated (1:1:1) into the 12-week Baduanjin exercise intervention (60 min per session, three sessions per week), the 12-week brisk walking group(60 min per session, three sessions per week) or the 12-week health education group. Primary outcome is the Fall-Risk Self-Assessment Questionnaire(FRQ), and secondary outcomes are fall efficacy index, gait assessment, balance function, lower limb muscle strength, cognitive function, activities of daily living(ADL) and MRI scans. In addition to the MRI scans, which will be measured before and after the intervention,other primary and secondary outcomes will be assessed at baseline, 6 weeks, and 12 weeks (at the end of the intervention) and after an additional 12-week follow-up period. The mixed linear model will be conducted to observe the intervention effects. Discussion This trial will investigate the effect of Baduanjin exercise on the prevention of falls in elderly individuals with MCI, explore the imaging mechanism of Baduanjin exercise to reduce the risk of falls in elderly individuals with MCI from the perspective of vestibular neural network, and provide strong evidence for Baduanjin exercise to reduce the risk of falls in elderly individuals with MCI, as well as provide new ideas and approaches for the central mechanism of Traditional Chinese Medicine(TRC) rehabilitation methods to intervene in falls in elderly. Trial registration Chictr.org.cn, ID: ChiCTR2200057520. Registered on 14 March 2022, https://www.chictr.org.cn/showproj.html?proj=146592 .